Sex, Gender-typing and Performance in 2015 JSC 3 Mathematics by Students in Gaborone - Nenty, Henty Johnson; Kgosidialwa, K.; Batsalelwang, K. J. (Advances in Social Sciences Research Journal, 2017)
An important reason why learners differ in their performance in mathematics is differences in the psychological environment created by socialization process presided over by their parents. Biologically sex makes learners differ physically and these differences are capitalized on, and that unevenly, through the gendering process which imposes different expectations on the male and female children. Hence differences in sex might not be as influencing on learners’ behavior as differences that result from the gendering process, for example, gender-typing of mathematics as a male subject. To test this speculation in the case of performance in mathematics a survey descriptive study using data from 735 students (298 boys and 437 girls) students who were taking the 2015 final JSCE examination from five randomly selected junior secondary schools in Gaborone was undertaken. Through testing two main null hypotheses it was found that girls, significantly more than boys, are more likely to gender-type mathematics as a male subject. The level to which the students perceive mathematics as a male subject has significant influence on their attitude towards the subject, the level to which they participate during lessons in mathematics classes, and their performance during the 2015 final JSCE examination in mathematics. Finally, sex was found to have a significant influence on the students’ performance during the 2015 final JSCE examination in mathematics, but such influence was less significant than that shown by level of gender-tying the subject. The findings were discussed and recommendations following from them were made.